Les ouvriers espagnols dans le mouvement social bas-pyrénéen, 1890-1914 - Emmanuel Plat (Les Cahiers de Framespa)
Population movements and trade on the border between France and Spain have existed for a very long time. Their nature partly changed in the late 19th century with economic immigration coming from the south. Many people came to find work as labourers and stopped in the Basses-Pyrénées. However, this call for foreign labour was not without problem in the workers’ world in construction. The ambivalent reactions of the local workers’ organizations confirm this. Nevertheless, xenophobia seems to have been contained and there was undeniably a partial integration of these foreign workers who participated in the formation of the local social movement.